Cot Keumuneng Village North Aceh Regency Apparatus Assistance in the Draft Qanun Formation on the Khalwat Prohibition: Pendampingan Aparatur Gampong Cot Keumuneng Kabupaten Aceh Utara Dalam Pembentukan Draft Qanun Larangan Khalwat - Nuribadah; Sofyan Jafar; Elidar Sari; Arif Rahman; Amrizal; Tri Widya Kurniasari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
The assistance provided to the Gampong apparatus or Tuha Peut in drafting the qanun on khalwat is necessary due to the limited knowledge of the Gampong officials regarding the proper formulation of a qanun. As an official institution within the Gampong governance system, the apparatus plays a role in advising and providing recommendations to the leader (Keuchik) on matters concerning customary law, traditions, and societal norms. One of the key functions of the apparatus at the village level is to draft and formulate qanuns. Khalwat is a social phenomenon that deeply disturbs the community and is considered a violation (Jarimah Khalwat). According to Qanun No. 6 of 2014, khalwat is defined as the act of being in a closed or hidden place between two individuals of different genders who are not mahram and without a marital bond, with mutual consent, leading to an act of adultery. This phenomenon is frequently occurring in Cot Keumuneng, making it necessary to establish rules encapsulated in a Qanun. Tuha Peut, or another equivalent term, refers to a representative body within the village that consists of religious scholars, customary leaders, community figures, and intellectuals. A socialization event regarding this matter was conducted. The material presented included Qanun No. 9 of 2008 on the Promotion of Customary Life and Traditions, as well as the procedures for the formulation of Gampong Qanuns. This initiative is expected to enhance the understanding and knowledge of Gampong officials to enable them to draft an effective qanun on khalwat.